ANALISIS DEMAND DAN ELASTICITY IMPLEMENTASINYA TERHADAP KEBIJAKAN HARGA - Jun Surjanti (UMSurabaya Publishing, 2010)
In this paper will be expanded discussion of the elasticity of demand, particularly in the real case that occurred, related to the policies that apply specifically to the case of sugar as a result of agricultural production. The case of sugar until very interesting discussion considering that there are various problems to be solved with economic studies and practical studies. In connection with Fridmen theory states that the actual purchase decision is based on income and the long period of time. Friedmen also argues that the existence of a temporary tax or any time, then the tax changes do not affect or small effect on the demand for consumer goods. This means that the tax does not affect spending patterns. Tax policy was actually causing problems sugar sugar availability nationally. Tax policy impact on the sugar turns over supply that ultimately led to the availability of the goods exceeds domestic needs. Further demand is expected to lower the sugar, besides the fact that it contradicts the theory of supply and demand, the price of sugar in the country to be expensive. This suggests that the problem of the gap between the expectations of theory, policy set and the fact that there are inconsistent. Meanwhile, from the consumer side, it turns out sugar is a requirement in elastic. Fridmen not explain the assumptions used by type of goods or elatis is elastic. In addition, consumers were not considering the duration and permanent income consumers do not consider in the decision to purchase sugar. Meanwhile, agricultural product tax relief in the long run it did not cause the mechanism of sugar prices running as it should, but instead result in increases in the price of sugar which harm consumers. Under existing conditions, Friedmen theory, the application should consider elatisitas an item. In addition, the government should set the highest price policy (Ceillling Price) to protect consumers.